STRATEGI MARKETING COMMUNICATION - Afriani, Anita (Universitas Prof. Dr. Moestopo (Beragama), 2015)
The purpose of this study was to determine the strategy used Marketing Communication PT. Primatama Nusa Indah Plaza Semanggi, knowing the internal activity Marketing Communication PT. Primatama Nusa Indah Plaza Semanggi and knowing the external activity Marketing Communication PT. Primatama Nusa Indah Plaza Semanggi.The theory used in this study were 7 CS by Scott M. Cutlip, namely the implementation of public relations strategies in communication. The method used in this research is descriptive qualitative paradigm PostPositivisme. Data collection techniques used in-depth interviews and observation. The results of this study indicate that the marketing communications strategy has been implemented by PT. Primatama Nusa Indah Plaza Semanggi by using a variety of print, electronic, and online via the official website plaza clover www.semanggi.com and fast response to complaints alerts when there is a complaint. Suggestions of researchers is preferably Marketing Communication PT. Primatama Nusa Indah PlazaClover does not just apply two elements of the strategy but the four elements of the strategy and add external activities in order to attract more public